Comparison of outcomes after carotid endarterectomy between type 2 diabetic and non-diabetic patients with significant carotid stenosis - Min-Jae Jeong; Hyunwook Kwon; Chang Hee Jung; Sun U. Kwon; Min-Ju Kim; Youngjin Han; Tae-Won Kwon; Yong-Pil Cho (Cardiovascular Diabetology, 2019)
Abstract Background We aimed to compare early and late outcomes after carotid endarterectomy (CEA) between Korean type 2 diabetic and non-diabetic patients and to investigate the impact of diabetes on the overall incidence of cardiovascular events after CEA. Methods We retrospectively analyzed 675 CEAs, which were performed on 613 patients with significant carotid stenosis between January 2007 and December 2014. The CEAs were divided into a type 2 diabetes mellitus (DM) group (n = 265, 39.3%) and a non-DM group (n = 410, 60.7%). The study outcomes included the incidence of major adverse events (MAEs), defined as fatal or nonfatal stroke or myocardial infarction or all-cause mortality, during the perioperative period and within 4 years after CEA. Results Patients in the DM and non-DM groups did not differ significantly in the incidence of MAEs or any of the individual MAE manifestations during the perioperative period. However, within 4 years after CEA, the difference in the MAE incidence was significantly greater in the DM group (P = 0.040). Analysis of the individual MAE manifestations indicated a significantly higher risk of stroke in the DM group (P = 0.006). Multivariate analysis indicated that diabetes was not associated with MAEs or individual MAE manifestations during the perioperative period, whereas within 4 years after CEA, diabetes was an independent risk factor for MAEs overall (hazard ratio [HR], 1.62; 95% confidence interval [CI] 1.06–2.48; P = 0.026) and stroke (HR, 2.55; 95% CI 1.20–5.41; P = 0.015) in particular. Conclusions Diabetic patients were not at greater risk of perioperative MAEs after CEA; however, the risk of late MAE occurrence was significantly greater in these patients. Within 4 years after CEA, DM was an independent risk factor for the occurrence of MAEs overall and stroke in particular.